Dynamic structure change of Cu nanoparticles on carbon supports for CO2 electro‐reduction toward multicarbon products. Issue 11 (11th July 2021) - Li, Qiang; Zhang, Yehui; Shi, Li; Wu, Mingliang; Ouyang, Yixin; Wang, Jinlan
Abstract: Cu nanoparticles with different sizes, morphology, and surface structures exhibit distinct activity and selectivity toward CO2 reduction reaction, while the reactive sites and reaction mechanisms are very controversial in experiments. In this study, we demonstrate the dynamic structure change of Cu clusters on graphite‐like carbon supports plays an important role in the multicarbon production by combining static calculations and ab‐initio molecular dynamic simulations. The mobility of Cu clusters on graphite is attributed to the near‐degenerate energies of various adsorption configurations, as the interaction between Cu atoms and surface C atoms is weaker than that of CuCu bonds in the tight cluster form. Such structure change of Cu clusters leads to step‐like irregular surface structures and appropriate interparticle distances, increasing the selectivity of multicarbon products by reducing the energy barriers of CC coupling effectively. In contrast, the large ratio of edge and corner sites on Cu clusters is responsible for the increased catalytic activity and selectivity for CO and H2 compared with Cu(100) surface, instead of hydrocarbon products like methane and ethylene. The detailed study reveals that the dynamic structure change of the catalysts results in roughened surface morphologies during catalytic reactions and plays an essential role in the selectivity of CO2 electro‐reduction, which should be paid more attention for studies on the reaction mechanisms. Abstract : The dynamic evolution process of the catalyst during catalytic reactions is highlighted. For carbon‐supported Cu clusters, the dynamic structure change leads to surface structure reconstruction and proper interparticle distance, which reduces the energy barriers of CC coupling effectively and improves the selectivity of multicarbon products.